Gestão da informação em repositórios institucionais: um estudo de caso da Biblioteca Digital do Ministério Público Federal Brasileiro - Valéria Regina da Silva (2020)
The present research corresponds a study of case applyed at Digital Library of Federal Public Prosecutor's Office and its general target is to carry out a brief analysis of the effectiveness of the BDMPF for the organization of information of the MPF. It is an exploratory research that brings a quantitative approach due analysis of the DSpace system statistics for visualizations, search and submission flow, beyond a qualitative approach. Makes use of the observation technique to analyze the studied scenario and application of interviews to the BDMPF directors. Beyond the use of bibliographic and documentary research to collect the information necessary to support research with reliable sources and with analysis of the policies and manuals adopted by the institution. It evaluates other public sector on the use of institutional repositories with a brief comparison between institutions. It presents the structure of the BDMPF through its collections and metadata and addresses proposals based on the use of controlled vocabularies, ontologies and taxonomies for a better representation of the existing knowledge in the database. It proposes some interventions to improve the platform and concludes with the library's audit report based on the ISO guidelines for auditing management systems and library performance indicators. Finally, it is intended to collect important datas guiding managers to assess the continuity or not of the BDMPF project, checking if there are multiple platforms and efforts that have the same functionality and purposes respectively.